Are we undertreating calcium deficiency in metabolic bone disease of prematurity? A case report and review - Boddu, Sirisha Kusuma; Lankala, Reena (Frontiers in Pediatrics, 2022)
Background: Both calcium and phosphorus supplements are needed to prevent and treat rickets of prematurity. However, the main focus of many treating neonatologists lies in supplementing predominantly phosphate and vitamin D. In this report, we describe a VLBW infant with severe metabolic bone disease (MBDP) and fractures due to inadequately treated underlying calcium deficiency and discuss the need to recognize and treat this entity. Case details and management: A 25-week, 700gm baby boy had an eventful neonatal period with respiratory distress syndrome, chronic lung disease, necrotizing enterocolitis, and apnea of prematurity. His treatment included total parenteral nutrition for four weeks, inhaled budesonide, furosemide, and caffeine. With high serum alkaline phosphatase (ALP: 1700 IU/L) and low phosphate (2.8 mg/dl), he was diagnosed with MBDP at 12 weeks, and started on oral phosphate and human milk fortifier, and was discharged. He also received 1400 IU/day of vitamin D. He was readmitted two weeks later with decreased lower limb mobility and respiratory distress. His X-rays showed radiological rickets with severe osteopenia of long bones and fractures of both femurs. Serum phosphate was 4.6 mg/dl but ALP was still high (1700 IU/L). He had hypocalcemia (6.2 mg/dl) and very high parathyroid hormone (PTH: 605 pg/ml) and 25-hydroxy Vitamin D (>200 ng/ml). The endocrinology team discontinued his phosphorus and vitamin D supplements, managed hypocalcemia initially with intravenous calcium gluconate, and later oral calcium citrate, and started calcitriol. Phosphorus supplements were added after the normalization of serum calcium. Over the next many weeks, serum phosphate, ALP, 25-hydroxy Vitamin D, and PTH normalized, and X-rays improved. Urine Ca/creatinine ratio stayed < 0.2 throughout this period. Discussion: MBDP results from both calcium and phosphate deficiencies, especially in VLBW infants with comorbidities. PTH, as a sensitive and early biomarker of calcium deficiency, can be a potential screening tool. Phosphorus supplementation without treating underlying calcipenia can be counterproductive and might precipitate hypocalcemia with disastrous consequences. In severe calcipenia, active vitamin D might have a role in addition to an appropriate dose of elemental calcium. Overzealous replacement of vitamin D in these infants can result in hypervitaminosis D.